KARAKTERISTIK PERPINDAHAN PANAS KONVEKSI ALAMIAH ALIRAN NANOFLUIDA AL2O3-AIR DI DALAM PIPA ANULUS VERTIKAL - Nazar, Reinaldy (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2016)
Results of several research have shown that nanofluids have better thermal characteristics compared to conventional fluid (water). In this regard, currently developing ideas for using nanofluids as an alternative heat transfer fluid in the reactor coolant system. Meanwhile the natural convection in a vertical annulus pipe is one of the important mechanisms of heat transfer and is found at the TRIGA research reactor, the new generation nuclear power plants and other energy conversion devices. On the other hand the heat transfer characteristics of nanofluids in a vertical annulus pipe has not been known. Therefore, it is important to do research continuously to analyze the heat transfer nanofluids in a vertical annulus pipe. In the research has been carried out numerical analysis by using computer code of CFD (computational of fluids dynamic) on natural convection heat transfer characteristics of nanofluids flow of Al2O3-water 2% volume in the vertical annulus pipe. The results showed an increase in heat transfer performance (Nusselt numbers - NU) by 20.5% - 35%. In natural convection mode with Rayleigh numbers 2.4708e+09 £ Ra £ 1.9554e+13 obtained empirical correlations for water is and empirical correlations for Al2O3-water nanofluids is .